Effect of early weaning on subsequent reproduction and calf production by replacement heifers - Busby, W.D.; McKee, M.; Corah, L.R. (Kansas State University. Agricultural Experiment Station, 2011)
Analysis of breeding records for 128 percentage Simmental females either weaned early (average age 63 days) or conventionally (average age 194 days) showed no statistically significant difference between early-weaned and nursed heifer calves for subsequent conception rate, calving date, ease of calving, calf birth weight, or 205-day adjusted calf weaning weight.
Keywords: Beef; Reproduction; Early weaning; Calf production; Replacement heifers